Geography, ontological politics and the resilient future. (March 2016) - Simon, Stephanie; Randalls, Samuel
Applications of 'resilience' have stretched it to the point of breaking, yet it still maintains a remarkable capacity to organize relations in diverse fields of geographical concern such as ecological management, development, security, psychology and urban preparedness. Critical takes on resilience have emphasized its neo-liberal roots and utility. Whilst we do not disagree with this stance, our critical intervention argues that there are multiple resiliences invoking differing spatialities, temporalities and political implications and that this multiplicity is an important part of the work that resilience can do. We explore diverse mobilizations of resilience thinking across a wide array of empirical domains drawing out the differing ontological bases of resiliences and the interventions meant to promote them, particularly given the tension between a desire for open, non-linearity on the one hand and a mission to control and manage on the other. Rather than take resilience to be a determinedly new shift in policymaking, we explore how the post-political qualities of 'resilience multiple' can enable changes in behaviours and practices that slide between conflicting and contestable visions of the good life and desirable futures. We argue that the only way to critically interrogate resilience is to force the question of particulars in its diverse articulations, and, thus, geographers should engage in debating the ontological politics of resilience multiple.